2022
DOI: 10.1155/2022/4819599
|View full text |Cite
|
Sign up to set email alerts
|

A Human Oral Fluid Assay for D- and L- Isomer Detection of Amphetamine and Methamphetamine Using Liquid-Liquid Extraction

Abstract: Medical providers are increasingly confronted with clinical decision-making that involves (meth)amphetamines. And clinical laboratories need a sensitive, efficient assay for routine assessment of D- and L-isomers to determine the probable source of these potentially illicit analytes. This paper presents a validated method of D- and L-isomer detection in human oral fluid from an extract used for determination of a large oral fluid assay (63 analytes) on an older AB SCIEX 4000 instrument. Taken from the positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Comparing the proposed EME method with sample preparation protocols reported in other chromatography‐based bioanalysis of amphetamine enantiomers, it is evident that the organic solvent consumption of the majority of reported methods is an order of magnitude higher than EME 40–44 . Notable exceptions are methods proposed by Chermá et al, 45 where urine was diluted with water, and by Hädener et al, 46 which employed on‐line column switching in combination with LC–MS.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Comparing the proposed EME method with sample preparation protocols reported in other chromatography‐based bioanalysis of amphetamine enantiomers, it is evident that the organic solvent consumption of the majority of reported methods is an order of magnitude higher than EME 40–44 . Notable exceptions are methods proposed by Chermá et al, 45 where urine was diluted with water, and by Hädener et al, 46 which employed on‐line column switching in combination with LC–MS.…”
Section: Resultsmentioning
confidence: 98%
“…Comparing the proposed EME method with sample preparation protocols reported in other chromatography-based bioanalysis of amphetamine enantiomers, it is evident that the organic solvent consumption of the majority of reported methods is an order of magnitude higher than EME. [40][41][42][43][44] Notable exceptions are methods proposed by Chermá et al, 45 where urine was diluted with water, and by Hädener et al, 46 (3:2 v/v) showed that carry-over was reduced in the latter injection solvent. In the present application, the total amphetamine concentration was known prior to the enantioselective analysis, and carry-over related issues could be circumvented by injection of blank samples.…”
Section: Evaluation Of Eme As Sample Preparationmentioning
confidence: 99%
“…Much of respiratory medicine is reliant on timely and precise diagnostics for critical This is significant to respiratory medicine because this technology can be used to supplement current syndromic-based tests and data can quickly and effectively be phenotypically characterized for clinical (co)infection and comorbid consideration. This has significance for laboratory medicine because it demonstrated this approach can rapidly be interpreted with a user-friendly and reliable platform for collective intention without overburdening laboratory investments in technology and people [75,76]. Furthermore, this approach could be advanced into a pan-microbial diagnostic testing that utilizes a single workflow for all specimen types.…”
Section: Discussionmentioning
confidence: 99%
“…Oral fluid drug testing is increasingly emerging as an alternative biological matrix for detecting drugs and monitoring patient medication compliance [4][5][6][7][8]. Moreover, in certain clinical situations clinicians may find oral fluid more beneficial for detection of specific drugs over UDT [9].…”
Section: Introductionmentioning
confidence: 99%